Comparative Antinociceptive Study of Leaf, Bark and Seed Extracts of Neem Collected from Aligarh District - Ahmad2, Syed Zia-ur-Rahman3, Zakia Khanam1, Ompal Singh2*, Jamal (Journal of Experimental Sciences, 2011)
Azadirachta indica (family Meliaceae) is commonly known as neem. The latinized name of neem A. indica (in Persian, Azadi = free, diracht = tree) literally meaning Ã¢â‚¬Å“the free tree of IndiaÃ¢â‚¬Â, is an alliteration for its being intrinsically free from insect and disease problems. The neem tree is considered as a Ã¢â‚¬Ëœsarvaroga nivariniÃ¢â‚¬â„¢ (the panacea for all diseases) and has also been hailed as Ã¢â‚¬Ëœheal allÃ¢â‚¬â„¢, Ã¢â‚¬Ëœdivine treeÃ¢â‚¬â„¢, Ã¢â‚¬Ëœvillage dispensaryÃ¢â‚¬â„¢ and Ã¢â‚¬ËœnatureÃ¢â‚¬â„¢s drugstoreÃ¢â‚¬â„¢. In an effort to elaborate the pharmacological properties of neem, comparative study of different extracts of neem (leaves, bark and seeds) has been done. The alcoholic extracts of leaf, bark and seed in dose 100 mg/kg showed significant antinociceptive activity. The alcoholic extract of leaves (duration 240 mimutes) showed most significant analgesic activity than other extracts.